Evolution of Jigsaw ‐ a National Youth Mental Health Service. Issue 5 (31st August 2021) - O'Reilly, Aileen; O'Brien, Gillian; Moore, Jeff; Duffy, Joseph; Longmore, Paul; Cullinan, Sarah; McGrory, Siobhán
Abstract: Aim: There has been a global movement towards transformation of youth mental health services, but limited information on the core principles and characteristics of these new services is available. Jigsaw is one such service, established in Ireland in 2006, with the intent of creating change in Ireland's system of mental healthcare for 12–25 year olds. The aim of this paper is to describe the evolution of Jigsaw services, which are now firmly embedded in the Irish system of care for young people, and recognized internationally as an established service network. Methods: This paper describes provides an up‐to‐date description of the Jigsaw service model, key areas of evolution that have shaped this model, and identifies future directions in service development. Results: Key attributes of the Jigsaw service model including therapeutic service, scope of practice, youth mental health promotion, youth participation, and monitoring/evaluation are described in this paper. Information on key enablers (funding and governance/quality) and service providers is also included. Conclusions: Information on the core principles and characteristics of youth mental health services is important. This paper addresses a gap in the literature by describing the Jigsaw service model, which continues to evolve so that it is responsive to the needs of young people.